Religion Materials Deconstruction on Student Books of Senior High School in Indonesia - Arrohmatan A (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2019)
This research aims to analyze material in the book student of Islamic and Character Education (PAI dan BP) curriculum 2013 for senior high school (SMA) grade XII perspective Deconstruction theory which was triggered by postmodern philosopher Jacques Derrida, Deconstruction is a concept that turned out that the new concepts and methodologies developed by approaches could be assimilated and integrated into more conventional forms of literary criticism without destroying or completely overturning text. This study uses naturalistic or qualitative method by technique library research. Because the problems those discussed in this research can only be answered by literature, and it is impossible to expect the data from field research. The results of the theoretical analysis that the material in this book contains the concepts of Deconstruction which was triggered by Jacques Derrida. Deconstruction has four kinds of traces, which in this research are indicators to analyzethis book. The four traces are the relative face of truth, truth belongs only to God, history cannot be measured, and non-absolute rationality. The scientific field of this book has four scientific fields, that is, Theology, Syariah, Sufism, and history